Comparison of 18F-Fluorocholine Positron Emission Tomography/Computed Tomography and Four-dimensional Computed Tomography in the Preoperative Localization of Parathyroid Adenomas-initial Results - Taywade, Sameer K. (Indian J Endocrinol Metab, 2017)
OBJECTIVE: We aimed to compare the diagnostic accuracy of 18F-Fluorocholine (FCH)-positron emission tomography/computed tomography (PET/CT) and four-dimensional (4D)- CT in detection and localization of eutopic and ectopic parathyroid adenoma (PA) in patients with hyperparathyroidism. MATERIALS AND METHODS: Five patients with primary hyperparathyroidism underwent FCH-PET/CT after 60 min of 185 MBq of intravenous 18F-FCH administration. Images were acquired from head to mediastinum at 3 min per bed position. No intravenous contrast was used. All patients underwent 4D-CT within 2 weeks of the FCH-PET/CT, with a precontrast, post contrast arterial, and venous phase with 75 ml intravenous Iohexol 350 followed by 25 ml saline chase. Histopathology was considered as the gold standard. RESULTS: Both modalities showed 100% concordance in the detection of parathyroid lesions. Both FCH-PET/CT and 4D-CT detected 7 lesions in 5 patients, with 4 patients having a single lesion, and 1 patient having three lesions. Of the 7 reported lesions, 4 were eutopic and 3 were ectopic. No additional lesions were detected by either modality in comparison to the other. All 7 specimens were resected and histopathology showed PA/hyperplasia. CONCLUSION: FCH-PET/CT and 4D-CT are equally efficacious in detection and localization of eutopic and ectopic PA. This may open up the possibility of using FCH-PET/CT in patients with negative conventional imaging who cannot undergo contrast studies.